E-Modul Based on Educational Tourism at Kilo 5 Luwuk Beach: Development of Learning Material to Faster Environmental Awareness in Junior High School Student - Moh. Fahri Haruna; Hasna Abdan; Frida Maryati Yusuf; Abubakar Sidik Katili (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Background: This research was initiated in response to the noticeable lack of environmental awareness among students in coastal regions, despite the area's abundant natural resources, and the absence of innovative, contextually relevant science learning tools. The research aims to develop a digital edutourism-based e-module at Kilo 5 Beach in Luwuk, designed to enhance students' conceptual understanding and foster environmental appreciation. Methodology: The research employs a Research and Development (R&D) approach, specifically the 4D development model (define, design, develop, and disseminate), though only three stages were executed: a preliminary study, design and validation by subject matter and media experts, and effectiveness testing with educators and students. Effectiveness was evaluated using pre- and post-tests, with data analyzed through the N-Gain formula and t-tests. Findings: This e-module is validated as educational resource. Expert validation confirmed the e-module's validity, with average scores exceeding 9%, indicating no revisions were needed. Practicality assessments revealed positive feedback from both teachers and students, with scores in the excellent category (above 90%), demonstrating the e-module's high practicality. The e-module's effectiveness was further evidenced by an increase in students' understanding, reflected in an N-Gain value of 0.6316 (medium category) and a significant t-test result (0.00<0.05). Contributions: This research provides empirical support for the use of educational tourism–based e-modules as contextual digital learning tools to improve environmental awareness and conceptual understanding among coastal junior high school students. It advances the 4D development framework by embedding local ecotourism contexts into science learning materials and evaluating their validity, practicality, and learning impact. The findings offer a transferable instructional approach that links formal science education with local environmental resources to support place-based and sustainability-focused learning.